Levitikus : Erster Teilband : 1 - 15, Zweiter Teilband : 16 - 27, Thomas Hieke : book review - Bosman, Hendrik Ludolph (Old Testament essays, 2015)
This impressive two volume commentary on a much neglected book in the Pentateuch is written by Thomas Hieke, since 2007 professor in OT at the Catholic Theological Faculty of the Johannes Gutenberg University in Mainz, Germany. Hieke studied Catholic Theology at the universities of Bamberg and Innsbruck and he wrote his doctoral dissertation on Ps 80 and the communal laments in the HB in 1994 under the supervision of Hubert Irsigler. During his appointment as Assistant Professor at Regensburg he completed his Habilitationschrift on the genealogies in Genesis, published in 2003. According to his personal blog (thomas.hieke.de) his current research interests are Biblical Theology and Exegesis, as well as the Synoptic Gospels.